EMPLOYEE PERFORMANCE REVIEWING FROM COMMUNICATION, WORK ENVIRONMENT AND STUDY COMPENSATION AT PT BINTER JET KARANGANYAR - Jeffrey Saputra; Eny Kustiyah; Bambang Mursito (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Developments economy and human resources are important values for a company. Companies can to improve and make plans about each other's performance to reach purpose of companies. The existence of research with the aim of looking at the effect of communication, work environment, and compensation on employee performance. Descriptive quantitative is used in research. Non-probability sampling was used in this study with a saturated sample method of 60 respondents. The analysis is multiple linear regression. The result is that communication has a positive effect on the performance of an employee, the work environment has a positive and significant influence on the performance of an employee and compensation has a positive and significant effect on an employee's performance.Meanwhile, the value of the coefficient of determination (R2) is known to be 31.8%, which means that employee performance is influenced by communication, environment, and compensation, then 68.2% is explained by other factors. Keywords: Employee performance, communication, work environment, compensation